Future Leaders in VUCA Bureaucracy: Millennials and Generation Z Perspective - Ramadhiani Firdaus, Sabilla (Indonesian Association for Public Administration (IAPA), 2024)
Civil servants in Indonesia are currently dominated by the productive age group, consisting of millennials (born in 1981-1996) at 2.32 million (52%) and Generation Z (born after 1997) at 268.9 thousand people (6%). Regarding to this number, the figure of future leaders is certainly developing, in line with the conditions of Millennials and generation Z (Gen Z) dominance, how cross-generational leaders can face the VUCA era in government bureaucracy. This research aims to find out the agile characteristics that future leaders must have from the perspective of Millennials and Gen Z, what future leaders must be like, and the strategies they must have to be able to survive and become winners in the VUCA era. This research uses a literature review, field research, and model formulation. This research reveals that the characteristics of future leaders must have agile leadership characteristics: integrity, effective communication skills, intelligent, emotional intelligence, visionary and resilience skill, privacy and work-life balance concern, good talent management skills, outward-looking and tech-savvy. Millennials and Gen Z visualize leaders who are not only capable and intelligent but deeply human-leaders who connect, listen, and support their teams while staying grounded in integrity and empathy, who can navigate both the complexities of modern life and the demands of a rapidly changing world.